1FENOMENA LINGKUNGAN DAN KUPU-KUPU DALAM LUKISAN REALIS - Drs. Irwan, M.Sn., Agung Kurnia, Drs. Erfahmi, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2016)
The purpose of this final project is to explore butterfly and environment phenomenon which is being threaten to be destroyed due to human activity on the earth through realist artwork. In its concept of manifestation, writer actualizes butterfly as main subject which illustrates the life of that insect. Writer illustrates butterfly and its environment that is contra with the real condition, writer presents artwork that relates to that problem in order to strengthen the concept. There are ten artworks in which explained the environment and butterfly phenomenon. That are: 1).Mulai Terhapus dari Tanah Tandus, 2). Tergusur, 3). Bisik yang Terusik (Bagian 1), 4). Bisik yang Terusik (Bagian 2), 5). Bisik yang Terusik (Bagian 3), 6). Sisa-Sisa Kebebasan, 7). Kisah Klasik, 8). Ironi Hidup, 9). Disingkir atau Menyingkir?, dan 10). Asa yang Sirna. Those artworks will apreciates the relation of environment and butterfly in order to educate people.Kata Kunci : Lingkungan, Kupu-Kupu, Seni Lukis, Realis